2021
DOI: 10.1101/2021.06.04.21257478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autoimmune profiling suggests paraneoplastic etiology in pediatric ROHHAD

Abstract: ROHHAD (Rapid-onset Obesity with Hypothalamic Dysfunction, Hypoventilation and Autonomic Dysregulation) is a rare, yet severe pediatric disorder resulting in hypothalamic dysfunction and frequent sudden death. Genetic and other investigations have failed to identify an etiology or diagnostic test. Frequent co-occurrence of neuroblastic tumors (NTs) and cerebrospinal fluid inflammation point to an autoimmune paraneoplastic neurological syndrome (PNS); however, specific anti-neural autoantibodies, a hallmark of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…PHOX2B mutations are absent similarly with other candidate genes like ASCL I, BDNF or HCRT [9], while partial response in some manifestations of hypothalamic disfunction has been achieved with immunoglobulins [10] and investigators have described an intrathecal synthesis of oligoclonal bands after CSF analysis [11], immune-cell infiltrates in the brain [12] and MRI signs of focal inflammation in the periaqueductal gray matter and hypothalamus [13]. Recently, Mandel-Brehm et al [14] have confirmed presence of autoantibodies to Zinc finger and SCAN domain-containing protein 1 (ZSCAN1) in 7 of 9 pediatric patients with tumor-associated ROHHAD. In our case, a complete panel for immune-mediated encephalitis was negative and immunoglobulins produced imperceptible results.…”
Section: To the Editormentioning
confidence: 99%
“…PHOX2B mutations are absent similarly with other candidate genes like ASCL I, BDNF or HCRT [9], while partial response in some manifestations of hypothalamic disfunction has been achieved with immunoglobulins [10] and investigators have described an intrathecal synthesis of oligoclonal bands after CSF analysis [11], immune-cell infiltrates in the brain [12] and MRI signs of focal inflammation in the periaqueductal gray matter and hypothalamus [13]. Recently, Mandel-Brehm et al [14] have confirmed presence of autoantibodies to Zinc finger and SCAN domain-containing protein 1 (ZSCAN1) in 7 of 9 pediatric patients with tumor-associated ROHHAD. In our case, a complete panel for immune-mediated encephalitis was negative and immunoglobulins produced imperceptible results.…”
Section: To the Editormentioning
confidence: 99%